Acute changes in cortical activation during active ankle movement after whole-body vibration for spasticity in hemiplegic legs of stroke patients: a functional near-infrared spectroscopy study. Issue 1 (2nd January 2020) - Miyara, Kodai; Kawamura, Kentaro; Matsumoto, Shuji; Ohwatashi, Akihiko; Itashiki, Yuki; Uema, Tomohiro; Noma, Tomokazu; Ikeda, Keiko; Shimodozono, Megumi
ABSTRACT: Background : A recent study revealed that whole-body vibration (WBV) tends to decrease spasticity in stroke-related hemiplegic legs. However, acute changes in cortical activation after WBV are unclear. Objective : To examine whether WBV induces acute changes in sensorimotor cortical activation in patients with stroke-related hemiplegic legs. Methods : Eleven stroke patients (mean age 52.6 [SD 15.4] years; median time after stroke 3 [25 th and 75 th percentiles; 3 and 10.5, respectively] months) participated in a comparative before-and-after intervention trial. Six healthy adults were also studied. WBV at 30 Hz was applied for 5 min to the hamstrings, gastrocnemius, and soleus muscles. Spasticity was assessed according to the modified Ashworth scale (MAS). Active and passive range of motion (A-ROM and P -ROM, respectively) were also measured. Change in Oxy-Hb concentration in bilateral sensorimotor cortex associated with voluntary ankle dorsiflexion of the affected limb was assessed via functional near-infrared spectroscopy (fNIRS) before and immediately after WBV. Results : MAS score, A-ROM, and P -ROM improved immediately after WBV. In the patients, while there was no significant interaction between effects of region (ipsilesional and contralesional sensorimotor cortex) and the WBV intervention (before and immediately after WBV) ( F 1, 10 = 0.702, p = .422), there was a significant main effect of the WBV intervention ( F 1, 10 = 6.971, p = .025). In the healthy participants, there was no association with the WBV intervention or region. Conclusions : In patients with stroke-related spastic-hemiplegic legs, WBV might result not only in clinical improvement but also in acute increase in sensorimotor cortical activation.